(untitled) (Res Medica, 2014)
Res Medica was to be scrapped at the last revision of the RMS laws. Yet despite its nonexistence for many years the suggestion to end it was met with a bizarre unease. Almost like ‘pulling the plug on a pal on life support’. A number of articles were written for a celebration copy to be printed for the 250th anniversary in 1987. Insufficient funding hampered its early resurrection and the journal of the Royal Medical Society slumbered on.